2012
DOI: 10.1021/ja300424h
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Catalyzed Bond Dissociation in an Anthracene Cyclophane Photodimer

Abstract: The anthracene cyclophane bis-anthracene (BA) can undergo a [4 + 4] photocycloaddition reaction that results in a photodimer with two cyclobutane rings. We find that the subsequent dissociation of the dimer, which involves the rupture of two carbon-carbon bonds, is strongly accelerated by the application of mild pressures. The reaction kinetics of the dimer dissociation in a Zeonex (polycycloolefin) polymer matrix were measured at various pressures and temperatures. Biexponential reaction kinetics were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 60 publications
10
78
1
Order By: Relevance
“…[34][35] PI is calculated to be only 87 kJ/mol above BA, again comparable to experimental values. 20 The higher energy of D-9TBA is likely due to the formation of two adjacent cylcobutene rings with higher strain than the two separate cyclobutane rings in PI. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 differences and volume changes, we would expect the high-energy, high-volume D-9TBA to be more sensitive to pressure than PI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35] PI is calculated to be only 87 kJ/mol above BA, again comparable to experimental values. 20 The higher energy of D-9TBA is likely due to the formation of two adjacent cylcobutene rings with higher strain than the two separate cyclobutane rings in PI. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 differences and volume changes, we would expect the high-energy, high-volume D-9TBA to be more sensitive to pressure than PI.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their enthalpic differences, the PI BA and D-9TBA 9TBA reactions have very similar activation energies of 93-96 kJ/mol at room temperature and pressure 20,[24][25]. Thus from an energetic standpoint, there is no reason to suspect that PI would become so reactive at high pressure relative to D-9TBA.…”
mentioning
confidence: 99%
“…where PD(t) corresponded to the time-dependent photo-dimerization degree, k 1 and k 2 were rate constants, and X 1 and X 2 were the relative weight fractions [31,32]. To be emphasized, the sum of X 1 and X 2 determined the maximum photodimerization extent (PD max ) that the coumarin pendants could reach after the long enough irradiation time [33].…”
Section: Resultsmentioning
confidence: 99%
“…Such endothermic chemistry with volume reduction could provide the desired capability of shockwave energy dissipation. One possible system with such characteristics is the anthracene molecule; Jezowski et al [21] have found that the application of mechanical force reduces the rection rate involved in chemical bond formation, while Slepetz et al [22] have calculated a possible intermediate pathway occurring between reactants and products, which involves molecular volume reduction. With the potential energy fully determined in terms of the system variables, we can write the system Hamiltonian from which we will derive equations of motion:…”
Section: Coarse Grain Description Of Coupled Thermo-mechano-chemical mentioning
confidence: 99%